Dual-mycorrhizal plants: their ecology and relevance - Teste, François P.; Jones, Melanie D.; Dickie, Ian A. (The New phytologist, 2020)
Dual-mycorrhizal plants are capable of associating with fungi that form characteristic arbuscular mycorrhizal (AM) and ectomycorrhizal (EM) structures. Here, we address the following questions: (1) Howmany dual-mycorrhizal plant species are there? (2) What are the advantages for a plant to host two, rather than one, mycorrhizal types? (3) Which factors can provoke shifts in mycorrhizal dominance (i.e. mycorrhizal switching)? We identify a large number (89 genera within 32 families) of confirmed dual-mycorrhizal plants based on observing arbuscules or coils for AM status and Hartig net or similar structures for EM status within the same plant species. We then review the possible nutritional benefits and discuss the possible mechanisms leading to net costs and benefits. Cost and benefits of dual-mycorrhizal status appear to be context dependent, particularly with respect to the life stage of the host plant. Mycorrhizal switching occurs under a wide range of abiotic and biotic factors, including soil moisture and nutrient status. The relevance of dual-mycorrhizal plants in the ecological restoration of adverse sites where plants are not carbon limited is discussed. We conclude that dual-mycorrhizal plants are underutilized in ecophysiological-based experiments, yet are powerful model plant–fungal systems to better understand mycorrhizal symbioses without confounding host effects.